Are Experts (News)Worthy? Balance, Conflict, and Mass Media Coverage of Expert Consensus. (3rd July 2020) - Merkley, Eric
ABSTRACT: Overlooked in analyses of why the public often rejects expert consensus is the role of the news media. News coverage of expert consensus on general matters of policy is likely limited as a result of journalists' emphasis in news production on novelty and drama at the expense of thematic context. News content is also biased toward balance and conflict, which may weaken the persuasiveness of expert consensus. This study presents an automated and manual analysis of over 280, 000 news stories on 10 issues where there are important elements of agreement among scientists or economists. The analyses show that news content typically emphasizes arguments aligned with positions of expert consensus, rather than providing balance, and only occasionally cites contrarian experts. More troubling is that expert messages related to important areas of agreement are infrequent even in relevant news content, and cues signaling the existence of consensus are rarer still.